Prophylaxis of Contrast-Induced Nephrotoxicity. (10th April 2014) - Ludwig, Ulla; Keller, Frieder
Abstract : Contrast-induced nephrotoxicity (CIN) is a form of acute kidney injury that follows intravascular contrast media exposure. CIN may be preventable because its risk factors are well established and the timing of renal insult is commonly known in advance. However, contrast-induced nephrotoxicity is still the third leading cause of iatrogenic renal failure. This important complication accounts up to 10% of acute renal failure cases in hospitalized patients and it is associated with increased short- and long-term morbidity and mortality. Prolonged hospitalization follows and overall increases healthcare resource utilization. This paper will discuss the various prophylactic procedures tested in clinical trials.